Joints and Problems of Property according to Hegel - Solari, Enzo (2021)
“Joints and Problems of Property according to Hegel”. Hegel’s theory of property according to the person’s abstract law in his Philosophy of Law states (a) that property is the external objectification of free will through appropriation (common or private) of exterior things; (b) that property does not only refer to a previously given world, but also to the absolute difference between persons and things and to the proto-economic problem of the persons’ access to things through their actions; (c) that the property that is rationally necessary for the free person-hood supposes the recognition between self-consciousness (even so the notions of recognition and objective spirit be improvable constructions with a detailed analytics both philosophical and empirical); and (d) that property, without refusing the typical formalism of private law, demands the concrete universality of public law, as also its access by all and each one, and its organization and universal distribution by means of institutional and governmental mechanisms.